A SURVEY ON RECENT TRENDS IN HEALTHCARE SYSTEMS. - Mrs. Mounica B, Neeraj2 & Abhinav3 (International Journal of Research Science and Management, 2017)
Technology plays a major role in monitoring various medical parameters and post operational days. The latest trend in Healthcare communication method using IoT is adapted. Internet of things (IoT) serves as a medium for the healthcare and plays important role in wide range of healthcare applications. A microcontroller is used as a gateway to communicate to the various sensors such as temperature sensor and pulse sensor. The sensor data is picked up by the microcontroller and sent to the network through Wi-Fi or Bluetooth and which provides real time monitoring of the health care parameters. The data is accessible to the doctors anytime. The controller is also connected with various alerting methods to alert the caretaker about variation in sensor readings. The prime concern in this method is that the data transmission to the destination has to be secure and made to allow only authorized users to access the data. The security issue can be addressed by transmitting the data through the password protected Wi-Fi module that will be encrypted by standard encryption methods and the users/doctor can access the data by logging to the HTML webpage. At the time of extremity situation alert message is sent to the doctor through GSM module triggered by the controller. This system is efficient with low power consumption capability, easy setup, high performance and time to time response.